Tuning stimulated emission properties of oligofluorene-based gain media via non-conjugation strategy. (February 2021) - Chang, Yong-Zheng; Zuo, Zong-Yan; Liu, Yu-Yu; Ou, Chang-Jin; Ding, Xue-Hua; Yang, Lei; Feng, Quan-You; Cao, Hong-Tao; Lin, Jin-Yi; Ren, Bao-Yi; Xia, Rui-Dong; Xie, Ling-Hai
Abstract: To uncover spiro-substitution effect in gain media, four types of spiro-terfluorene derivatives, in which two individual conjugation chains with different conjugation length were connected via spirofluorene-9, 9′-xanthene (SFX) and spirobifluorene (SBF) units, have been designed and synthesized. All spiro-terfluorene derivatives display high photoluminescent quantum yield (PLQY) and radiative transition rate (Kr ) in solution. The PLQY and Kr gradually increase in the spin-coating films of 2SFX-SBF, 3SFX-SBF and 4SFX-SBF, clearly indicating that the lateral spiro-substitution can effectively suppress aggregation-induced exciton quenching. As a result, 4SFX-SBF with two identical conjugation chains possesses the best amplified spontaneous emission (ASE) performance with a low threshold of 0.28 μJ/cm 2 and high gain coefficient of 159 cm −1 . In addition, the spiro-terfluorenes display outstanding thermal stability, and the ASE threshold only doubles after 150 °C annealing. Hence, the lateral spiro-substituted strategy would be an intriguing strategy to design high-gain and low-threshold media for organic lasers. Graphical abstract: Image 1 Highlights: Four spiro-terfluorenes with identical conjugation length derivatives are synthesized. The compounds have high radiation transition rate and gain coefficient of 159 cm −1 . 4SFX-SBF with two identical conjugation chains possesses lowest ASE threshold of 0.28 μJ/cm 2 .